The role of proactive marketing in customer happiness: an analytical study of the opinions of a sample of employees in some private banks (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The current study aimed to know the role of proactive marketing in customer happiness in Iraqi private banks. To achieve the study objectives, the descriptive analytical approach was adopted, as the researchers developed a questionnaire consisting of (29) paragraphs, and a random sample was drawn so that the study sample consisted of (89) employees in (the National Islamic Bank, International Development and Iraqi Islamic Bank) from a total of (415) employees, and the results were analyzed based on the (SPSS) program and descriptive statistics tools. It was concluded that private banks currently have a great interest in marketing their banking services proactively and have the ability to bear risks and innovate in providing new banking services characterized by high flexibility, and are constantly looking for new opportunities. There is a correlation and influence between proactive marketing and customer happiness. The most prominent recommendations of the research were the necessity for private bank administrations to adopt proactive marketing to meet the needs and requirements of customers and provide services at the required speed, in addition to proposing new services that satisfy customers in a way that achieves their happiness in the long term.